Association between misalignment of circadian rhythm and obesity in Korean men: Sixth Korea National Health and Nutrition Examination Survey. (1st February 2020) - Kim, Ho Jun; Choi, Seulggie; Kim, Kyuwoong; Park, Hyungjun; Kim, Kyae-Hyung; Park, Sang Min
ABSTRACT: Background : The disruption of circadian rhythm has been found to associate with obesity in vivo and in vitro. Sleep duration, eating habits, total feeding time, and nightshift work can also affect circadian rhythms. This study investigated the association between misalignment of circadian rhythm and obesity in Korean men, using a cross-sectional database. Methods : This study used data from the Korean National Health and Nutrition Examination Survey (KNHANES), whose study population was 3, 658 men aged 18 to 60 years. General and abdominal obesity was defined as a body mass index (BMI) ≥ 25 kg/m 2 and waist circumference ≥ 90 cm, respectively. Circadian rhythm factors were determined with a self-report questionnaire and included breakfast frequency, sleep duration, and work time. Frequency of breakfast was divided into regular breakfast (five to seven times a week) and irregular breakfast (less than five times a week). Sleep duration was divided into less than 7 hours, 7–9 hours, and over 9 hours. Working time was defined as day/evening, night shift, and other type. The adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for general and abdominal obesity were calculated using multivariable logistic regression according to the number of factors that disturb the circadian rhythm. Results : Participants with 1 (aOR 1.34, 95% Cl 1.10–1.61) and ≥2 (aOR 1.62, 95% Cl 1.29–2.05) factors disturbing circadian rhythms were associated with elevated risk for general obesity. Similarly, those with 1 (aOR 1.33, 95% Cl 1.09–1.63) and ≥2 (aOR 1.70, 95% Cl 1.32–2.20) factors had elevated risk for abdominal obesity. Conclusions : Factors disturbing the circadian rhythm were associated with general and abdominal obesity. Additional studies are needed, and associations with metabolic diseases should be investigated.